(untitled) (Swiss Medical Weekly, 2015)
QUESTION UNDER STUDY: What are the trends in avoidable cancer mortality in Switzerland and neighbouring countries? METHODS: Mortality data and population estimates 1996–2010 were obtained from the Swiss Federal Statistical Office for Switzerland and the World Health Organization Mortality Database (http://www.who.int/healthinfo/mortality_data/en/) for Austria, Germany, France and Italy. Age standardised mortality rates (ASMRs, European standard) per 100 000 person-years were calculated for the population <75 years old by sex for the following groups of cancer deaths: (1) avoidable through primary prevention; (2) avoidable through early detection and treatment; (3) avoidable through improved treatment and medical care; and (4) remaining cancer deaths. To assess time trends in ASMRs, estimated annual percentage changes (EAPCs) with 95% confidence intervals (95% CIs) were calculated. RESULTS: In Switzerland and neighbouring countries cancer mortality in persons <75 years old continuously decreased 1996–2010. Avoidable cancer mortality decreased in all groups of avoidable cancer deaths in both sexes, with one exception. ASMRs for causes avoidable through primary prevention increased in females in all countries (in Switzerland from 16.2 to 20.3 per 100 000 person years, EAPC 2.0 [95% CI 1.4 to 2.6]). Compared with its neighbouring countries, Switzerland showed the lowest rates for all groups of avoidable cancer mortality in males 2008–2010. CONCLUSION: Overall avoidable cancer mortality decreased, indicating achievements in cancer care and related health policies. However, increasing trends in avoidable cancer mortality through primary prevention for females suggest there is a need in Switzerland and its European neighbouring countries to improve primary prevention.